2019
DOI: 10.1088/1361-648x/ab03ef
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroicity and magnetoelectric coupling in the paramagnetic state of the metal-organic framework [(CH3)2NH2]Ni(HCOO)3

Abstract: The metal-organic framework [(CH 3 ) 2 NH 2 ]Ni(HCOO) 3 (DMA-Ni) has an ABX 3 perovskitelike structure. At T C ~ 181 K, DMA-Ni displays a first-order ferroelectric transition, which is triggered by the disorder-order transition of hydrogen bonds. In addition, this compound exhibits a spin-canted antiferromagnetic order below T N ~ 37.6 K through the long-distance superexchange interaction, and a spin-reorientation transition appears near 15 K. The coexistence of magnetic and ferroelectric orders at low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Apart from the multiferroic state, the ME effect can exist in any other magnetic orders and even in the paramagnetic state. The PME effect was also observed in the multiferroic MOF [(CH 3 ) 2 NH 2 ]Ni(HCOO) 3 [38] and hybrid organometallic system NH 2 (CH 3 ) 2 Al 1−x Cr x (SO 4 ) 2 × 6H 2 O. [92] Recently, Long et al achieved a strong room-temperature ME coupling (α 31 = ∼100 mV Oe −1 cm −1 ) in a paramagnetic ferroelectric ytterbium (III) coordination complex.…”
Section: Formate-based Multiferroic Mofsmentioning
confidence: 70%
See 1 more Smart Citation
“…Apart from the multiferroic state, the ME effect can exist in any other magnetic orders and even in the paramagnetic state. The PME effect was also observed in the multiferroic MOF [(CH 3 ) 2 NH 2 ]Ni(HCOO) 3 [38] and hybrid organometallic system NH 2 (CH 3 ) 2 Al 1−x Cr x (SO 4 ) 2 × 6H 2 O. [92] Recently, Long et al achieved a strong room-temperature ME coupling (α 31 = ∼100 mV Oe −1 cm −1 ) in a paramagnetic ferroelectric ytterbium (III) coordination complex.…”
Section: Formate-based Multiferroic Mofsmentioning
confidence: 70%
“…Many cations such as (NH 4 ) + , [29] (C 3 N 2 H 5 ) + , [30] C(NH 2 ) 3 + , [31] (CH 3 CH 2 NH 3 ) + , [25] (CH 3 NH 2 NH 2 ) + , [46] and (CH 3 NH 3 ) + [28] have been chosen as the A cations. Meanwhile, many divalent metal ions have been placed at the B-site, such as Mn 2+ , [34] Fe 2+ , [35][36] Co 2+ , [28] Ni 2+ , [37,38] Zn 2+ , [86] Cu 2+ , [31] Cd 2+ , [87] Mg 2+ , [88] and Cr 2+ . [80] Cu 2+ [84] and Cr 2+ [80,89] are also famous as Jahn-Teller-active ions.…”
Section: Multiferroicity Of Inorganic-organic Hybrid Compoundsmentioning
confidence: 99%
“…As a result, the magnetic structure of MnNi-MOF can be assigned to canted antiferromagnetic (CAFM). The T N of Mn-MOF is 8.7 K and Ni-MOF is 37 K. , The intermediate magnetic ordering temperature of 13 K represents the modified Mn–O–C–O–Mn superexchange pathway in MnNi-MOF. These magnetic measurements indicate that replacing larger Mn 2+ by smaller Ni 2+ induces significant changes in C–O bonds and O–C–O bond angles of the organic linker HCOO – .…”
Section: Resultsmentioning
confidence: 99%
“…The similar magnetic field enhancement of polarization was also observed in Ni-MOF. 31 This magnetic field induced enhancement of polarization is an interesting aspect in MOFs and is still under debate. Surprisingly, in MnNi-MOF, the magnetic field suppresses the polarization from 0.91 μC/cm 2 at 0 T to 0.72 μC/cm 2 at 5 T with the negative static ME coefficient estimated to be −496 ps/m.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous studies have shown that ferroelectric or antiferroelectric phase transitions are triggered by the order–disorder of A site organic cations inside the cavities through hydrogen bonding in [(CH 3 ) 2 NH 2 ] M (HCOO) 3 (M = divalent metal ions)-type compounds. The organic linkers X bridging metal ions via coordination bonds form three-dimensional soft networks, giving rise to sensitivity to the external pressure which provides plenty of opportunities in control of structure merits and functionality, such as hydrogen bond arrangement, structural phase transition, and melting temperature modification. …”
mentioning
confidence: 99%